Resisting allegory : interpretive delirium in Spenser's Faerie Queene - Berger, Harry, Jr., 1924-2021; Miller, David Lee, 1951- (New York : Fordham University Press, 2020)
In Resisting Allegory, the leading Spenser critic of our time sums up a lifelong commitment to the theory and practice of textual interpretation. Central to this volume is an attention to the deployment of gender in conjunction with the Berger's notion of narrative complicity, all built on close attention to the text.
Frontmatter -- Contents -- Editor's introduction -- Introduction. On texts and countertexts -- Chapter 1. Displacing autophobia in the faerie queene, book 1: ethics, gender, and oppositional reading in the spenserian text -- Chapter 2. Narrative as rhetoric in the faerie queene -- Chapter 3. Wring out the old: squeezing the text, 1951-2001 -- Chapter 4. Resisting translation: britomart in book 3 of spenser's faerie queene -- Chapter 5. Actaeon at the hinder gate: the stag party in Spenser's gardens of Adonis -- Acknowledgments -- Notes -- Index
Includes bibliographical references and index.
Print version record
eBooks on EBSCOhost
Keywords: Spenser, Edmund, -- 1552?-1599 -- Criticism and interpretation; Spenser, Edmund, -- 1552?-1599.; Spenser, Edmund, -- 1552?-1599; Faerie queene (Spenser, Edmund); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Spenser; The Faerie Queene; allegory; the New Criticism; theory of interpretation; Electronic books; Criticism, interpretation, etc